Motivational strategies reduce recidivism and enhance treatment adherence in intimate partner violence perpetrators with substance use problems - Marisol Lila; Cristina Expósito-Álvarez; Manuel Roldán-Pardo (Frontiers in Psychiatry)
IntroductionThe incorporation of motivational strategies has shown promising results in increasing the effectiveness of intervention programs for intimate partner violence perpetrators, such as enhancing treatment adherence and decreasing risk of intimate partner violence recidivism. This could be particularly important for participants with alcohol and/or other drug use problems (ADUPs), who are at higher risk of recidivating and dropping out from the intervention. Consequently, there is a need to study whether motivational strategies are also effective for high-risk and highly resistant participants. The aim of this study was to determine whether the incorporation of motivational strategies led to improved outcomes in participants with ADUPs compared to those without.MethodsParticipants were intimate partner violence male perpetrators who received a standard intervention (n = 349) or a standard intervention adding an individualized motivational plan (n = 367). Data on official intimate partner violence recidivism, intervention dose, and dropout were collected after the end of the intervention. Comparisons were made between participants with and without ADUPs in each intervention condition.ResultsResults showed that in the full sample of participants, irrespective of their condition, those with ADUPs presented a higher recidivism (p = .007) and dropout rate (p = .003) and lower intervention dose than those without ADUPs (p = .005). When only considering participants in the standard intervention, results also showed that intimate partner violence perpetrators with ADUPs had a higher recidivism (p = .025) and dropout rate (p = .015) and lower intervention dose (p = .048) than those without. However, there were no significant differences between participants with and without ADUPs in the standard intervention adding an individualized motivational plan.DiscussionWhen incorporating motivational strategies into the standard interventions for intimate partner violence perpetrators, disparities between participants with and without ADUPs were mitigated. Specifically, participants with ADUPs showed similar outcomes to those without ADUPs after receiving the standard intervention adding an individualized motivational plan. Our results suggest that motivational strategies may be effective in reducing intimate partner violence recidivism and improving treatment adherence in high-risk and highly resistant intimate partner violence perpetrators.